Integrative Post-event Impact Assessment Framework for Volcanic Eruptions: A Disaster Forensic Investigation of the 2011–2012 Eruption of the Cordón Caulle Volcano (Chile) - Dominguez, Lucia; Bonadonna, Costanza; Frischknecht, Corine; Menoni, Scira; Garcia, Alexander (Frontiers in Earth Science, 2021)
Understanding the complexity of future volcanic impacts that can be potentially induced by the large variability of volcanic hazards and the multiple dimensions of vulnerability of the increasingly interdependent and interconnected societies, requires an in-depth analysis of past events. A structured and inclusive post-event impact assessment framework is proposed and applied for the evaluation of damage and disruption on critical infrastructures caused by the eruption of the Cordón Caulle volcano (Chile) in 2011–2012. This framework is built on the forensic analysis of disasters combined with the techniques of the root cause analysis that converge in a bow-tie tool. It consists of a fault tree connected to subsequent event trees to describe the causal order of impacts. Considering the physical and systemic dimensions of vulnerability, four orders of impact have been identified: i) the first order refers to the physical damage or the primary impact on a component of the critical infrastructure; ii) the second order refers to the loss of functionality in the system due to a physical damage on key components of the system; iii) the third order refers to the systemic impact due to the interdependency and connectivity among different critical infrastructures; and iv) a higher order is related to the consequences on the main economic sectors and to social disruption that can activate an overall damage to the economy of the country or countries affected. Our study in the Argentinian Patagonia shows that the long-lasting impact of the 2011–2012 Cordón Caulle eruption is mostly due to a secondary hazard (i.e., wind remobilisation of ash), which exacerbated the primary impact affecting significantly larger areas and for longer time with respect to primary tephra deposition. In addition, systemic vulnerability, particularly the intrinsic dependencies within and among systems, played a major role in the cascading impact of the analysed communities.